PENGARUH PENGUASAAN TATA BAHASA DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENULIS DESKRIPSI BAHASA INGGRIS (Survey pada SMPN di Kota Bekasi) - Yanti - Rosalinah (Wanastra: Jurnal Bahasa dan Sastra, 2017)
The purpose of this study was to: determine the interactive effect of grammar mastery and motivation trait towards descriptive English writing skill. Sample size of 80 students, and the sampling technique used is simple random sampling. Research instruments used were the test results of motivation trait and descriptive English writing skill scoring that have been tested regression coefficient value of 0,008 and 1,738. The used test is multiple regression analysis. The results showed: 1) There are significant interactive effects of grammar mastery and motivation trait towards descriptive English writing skill as Fobserved = 29,981 > Ftable 2,72 at the 5% significance level. 2) There is a significant effect of grammar mastery towards descriptive English writing skill, as tobserved = 4,000 > ttable = 1,684 at the 5% significance level. 2) There is a significant effect of motivation trait towards descriptive English writing skill as tobserved = 7,703 > ttable = 1,671 at the 5% significance level. The results contribute most to the increasing of descriptive English writing skill by grammar mastering and increasing the motivation. Keywords: Grammar Mastery, Motivation, Descriptive Writing Skill